PENERAPAN METODE ROOT CAUSE FAILURE ANALYSIS DAN PENGUJIAN PADA PERBAIKAN QUICK TOOL CHANGE SYSTEM DI MESIN FEHLMANN P18s - Feriadi, Indra; Ariyanto, Ariyanto; Daffa, Muhammad; Arwansyah , Rifki (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
This study aims to analyze and repair damage to the Fehlmann P18s milling machine No. 04 used in the Mechanical Laboratory of Polman Babel. The machine was inoperable due to electrical system failure and a malfunction in the Quick Tool Change System (QTCS). A Root Cause Failure Analysis (RCFA) method using the 5 Why analysis was applied to identify the root causes. The investigation revealed failures in electrical components such as contactors, selector switches, push buttons, fuses, capacitors, and diodes caused by unstable current. Furthermore, the QTCS could not clamp the tool holder properly due to corrosion on spindle components, bearings, and housing. The repair process involved replacing and cleaning damaged parts, followed by re-testing including geometric and functional tests. The testing showed that the machine was successfully restored to its operational state and complied with geometric precision standards. As a preventive measure, a time-based preventive maintenance plan was developed for both the electrical system and the QTCS to avoid recurring failures. This project proves that the RCFA method is effective in analyzing machine issues systematically and comprehensively.